Pedagogical content knowledge of argumentation: Using classroom contexts to assess high‐quality PCK rather than pseudoargumentation. Issue 2 (26th May 2015) - McNeill, Katherine L.; González‐Howard, María; Katsh‐Singer, Rebecca; Loper, Suzanna
Abstract: Despite the recent emphasis on science practices, little work has focused on teachers' knowledge of these key learning goals. The development of high quality assessments for teachers' pedagogical content knowledge (PCK) of science practices, such as argumentation, is important to better assess the needs of teachers and to develop supportive teacher education experiences. In this paper, we present lessons learned from a development process to conceptualize, design, and pilot a measure of teachers' PCK of argumentation. We use the results from our pilot test with 103 middle school science teachers, cognitive interviews with 24 middle school science teachers, and feedback from 10 advisors to present these lessons learned. Specifically, this work resulted in the refinement of our conceptualization of PCK of argumentation in two areas: (1) Moving beyond pseudoargumentation of surface level features to target the quality of structural components and students' dialogic interactions as well as the use of instructional strategies that align with student needs and (2) Focusing on dialogic argumentation in terms of the quality of student interactions in which they build off of and critique each others' claims, rather than goals such as persuasion that are difficult to observe. In addition, the iterative design process suggested that PCK of argumentation assessments should use classroom contexts (such as vignettes, student writing, and video) to activate teachers' knowledge in use by connecting to their prior experiences; however, the student argumentation examples need to highlight one specific strength or challenge and provide sufficient detail around the example to focus the assessment item. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 53: 261–290, 2016.